2017
DOI: 10.2174/1874613601711010024
|View full text |Cite
|
Sign up to set email alerts
|

Plasma IP-10 Concentrations Correlate Positively with Viraemia and Inversely with CD4 Counts in Untreated HIV Infection

Abstract: Background:Chronic immune activation is a feature of HIV infection associated with accelerated HIV disease progression. There is conflicting data on the association of biomarkers of immune activation with traditional markers of HIV disease progression; CD4 counts and viral load (VL).Objective:The study aimed to determine the association of biomarkers of immune activation; interferon (IFN)-γ-induced protein 10 (IP-10) and soluble cluster of differentiation 14 (sCD14) in chronic HIV infection with traditional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…Given these observations, we hypothesized that this reduction in HGS would be associated with the inflammatory status caused by high viremia. This hypothesis is supported by a previous study, which found a relationship between IP-10 concentrations with high VL, even suggesting that this biomarker may be associated with HIV pathogenesis and immune depletion (48). In addition, our findings also corroborate those found in the substudy, suggesting that VL cumulative increased exposure seems to be an important factor in the decline in HGS, and further highlights the importance of early initiation of ART (14).…”
Section: Discussionsupporting
confidence: 91%
“…Given these observations, we hypothesized that this reduction in HGS would be associated with the inflammatory status caused by high viremia. This hypothesis is supported by a previous study, which found a relationship between IP-10 concentrations with high VL, even suggesting that this biomarker may be associated with HIV pathogenesis and immune depletion (48). In addition, our findings also corroborate those found in the substudy, suggesting that VL cumulative increased exposure seems to be an important factor in the decline in HGS, and further highlights the importance of early initiation of ART (14).…”
Section: Discussionsupporting
confidence: 91%
“…This inflammatory factor is considered to be a biomarker of chronic immune activation and as a marker for disease progression during HIV infection. It has recently been reported to suppress T cell and NK cell function in HIV-infected patients ( Mhandire et al, 2017 , Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cross sectional study which was nested in the "Immunological and Virological Investigations of HIV-infected individuals with CD4 counts above 350 cells/µL (IVIHIV)" prospective cohort study as described elsewhere [24]. Briefly, the IVIHIV study was conducted at the Parirenyatwa Group of Hospitals Opportunistic Infections Clinic, in Harare, Zimbabwe.…”
Section: Study Participants and Specimen Collectionmentioning
confidence: 99%
“…CD4+ T lymphocytes were enumerated in EDTA anti coagulated whole blood within 6 hours of blood collection in the IVIHIV study using the Partec platform (Sysmex, Görlitz, Germany) as we described elsewhere [24]. Plasma HIV load was also estimated in the IVIHIV study from the archived plasma using the Cavidi Exavir viral load version 3 assay (Cavidi AB, Uppsala Science Park, Sweden) following the manufacturer's instruction.…”
Section: Measurement Of Cd4 Counts and Plasma Viral Loadmentioning
confidence: 99%
See 1 more Smart Citation